The Evaluation of the Fourth Grade Students' Performance in Preparing and Drawing Maps of Iraq: (Applied Cartographic Study Includes Departments of Geography at Colleges of Arts, Education (Ibn Rushd), and Education Girls- University of Baghdad) - Al-Akidi, Wissam Ahmed (Al-Adab Journal, 2021)
The aim of the research is to evaluate the performance of fourth grade students in departments of Geography in drawing geographical maps and identifying geographical phenomena in a precise scientific manner, with emphasis on the need to use (map elements) in drawing.The map of Iraq was the sample used in the research.The researcher adopted the field study (tests) in the department of Geography in three colleges at University of Baghdad, namely (Arts, Education (Ibn Rushd), and Education for Girls). The sample size was about (125) students in each department, so the total number of students was (375) students, which contributed to give a clear picture about students' performance.The main point at which the research reached is that there are good aspects in drawing maps and identifying geographical phenomena, but not at the required level. Still some other aspects are met with a great failure due to a number of reasons such as adopting old methods, the lack of financial support, and the lack of new scientific programs which contribute in raising the level of students' performance in drawing maps. Another reasons why students are not at the required level is ascribed to the fact of not adopting the tests in drawing maps, and also the absence of specialized professors as in the Department of Geography (College of Education for Girls).